Enfranchised Africans and disfranchising legislations : an analysis of the educated landowners of Queenstown as an African middle class, c.1872-1909. - Visser, Beaurel (Stellenbosch : Stellenbosch University, 2021)
Thesis (MA)--Stellenbosch University, 2021.